Third text. ([London Kala Press, 1987)
"Third World perspectives on contemporary art & culture."
Published <Mar. 2002-> by: Routledge.
Title from cover.
Some issues have also distinctive titles.
Latest issue consulted: 87, Vol. 21, issue 4 (July 2007).
Issues for 58 (Mar. 2002)- also have numbering vol. 16, no. 1-
Keywords: Art and society |v Periodicals; Art -- 20th century -- Developing countries -- Periodicals; Developing countries -- Intellectual life -- Periodicals